An Interactive Review on the Role of Tocotrienols in the Neurodegenerative Disorders - Naomi, Ruth; Shafie, Nurul Husna; Kaniappan, Priyatharisni; Bahari, Hasnah (Frontiers in Nutrition, 2021)
Neurodegenerative disorders such as Parkinson’s and Alzheimer’s disease are claimed to be major concern causing a significant disease burden worldwide. Oxidative stress, mitochondrial dysfunction and nerve dam-age are the main reasons for the emergence of these diseases. The formation of reactive oxygen species (ROS) is the common chemical molecule that is formed from all these three interdependent mechanisms which is high-ly reactive towards the neuronal cells. For these reasons, administration of tocotrienols (T3s) which are a po-tent antioxidant is proven to cater this problem, through in vitro and in vivo investigations. Interestingly, their therapeutic potential not only limited to antioxidant property but are also able to reverse the neuronal damage and could act as a shield for mitochondria dysfunction. Thereby, T3s prevent the damage to the neurons. In regards to this statement, in this review, we focused on summarizing and discussing the potential therapeutic role of T3s on Alzheimer’s and Parkinson’s diseases, and their protective mechanisms based on evidence from the in vitro and in vivo studies. However, there is no any clinical trial conducted to prove the efficacy of T3s for Alzheimer’s and Parkinson’s subjects. As so, the therapeutic role of T3s for these neurodegenerative disorders is still under debate.